Why isn't South Africa Growing Faster? : A Comparative Approach - Eyraud, Luc (IMF Working Papers; Working Paper ;, 2009)
The purpose of this paper is to examine factors that have constrained South Africa's growth since the end of apartheid by comparing its GDP components and its saving and investment performance with those of 10 faster-growing countries. The study finds that sluggish investment has undermined growth since 1996 and that the underinvestment is in part explained by limited saving. Thus, over the last decade, interactions between investment, saving, and production may have perpetuated slow growth in South Africa.